2021
DOI: 10.3389/fphar.2021.649581
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine Ameliorates Peritoneal Angiogenesis by Regulating VEGF/Hippo/YAP Signaling

Abstract: Angiogenesis of human peritoneal vascular endothelial cells (HPVECs), linked to vascular endothelial growth factor (VEGF)/VEGF receptor 2 (VEGFR2) signaling, is a complication of peritoneal fibrosis (PF). Hippo/YAP signaling interacts with VEGF/VEGFR2 signaling, but the effect on peritoneal angiogenesis and PF has not been studied. We tested VEGF/Hippo/YAP inhibition by tetramethylpyrazine (TMP) in PF mice and HPVECs. This treatment ameliorated peritoneal dialysis (PD)–induced angiogenesis and PF. In mice, PF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Bosutinib, a tyrosine kinase inhibitor, significantly decreased the level of the phosphorylation of YAP at tyrosine 357 (Y357) and YAP activation to alleviate endothelium injury and the development of atherosclerosis (25). Likewise, salvianolic acid B, harmine and tetramethylpyrazine, the extracts from the traditional medicinal plants, inhibited YAP nuclear translocation and activation, and thus played a potent atheroprotective role (8,9,53). These inhibitor and extracts from the traditional medicinal plants might serve as potential therapeutical candidates for improving endothelial function and cardiovascular diseases via regulating the YAP/TAZ pathway.…”
Section: Effect Of Drugs On Yes-associated Protein/transcriptional Co...mentioning
confidence: 99%
“…Bosutinib, a tyrosine kinase inhibitor, significantly decreased the level of the phosphorylation of YAP at tyrosine 357 (Y357) and YAP activation to alleviate endothelium injury and the development of atherosclerosis (25). Likewise, salvianolic acid B, harmine and tetramethylpyrazine, the extracts from the traditional medicinal plants, inhibited YAP nuclear translocation and activation, and thus played a potent atheroprotective role (8,9,53). These inhibitor and extracts from the traditional medicinal plants might serve as potential therapeutical candidates for improving endothelial function and cardiovascular diseases via regulating the YAP/TAZ pathway.…”
Section: Effect Of Drugs On Yes-associated Protein/transcriptional Co...mentioning
confidence: 99%
“…VP can inhibit YAP transcriptional activity in the Hippo pathway, resulting in the regulation of tissue development. Emerging studies have revealed an underlying convergence between VEGF and Hippo-YAP signaling, which has yet to be utilized in clinical applications [ [19] , [20] , [21] , [22] ]. YAP signaling could act as a hinge to mediate the downstream proangiogenic phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Williams et al (2002) performed the first comprehensive cross-sectional analysis of the morphological changes in the peritoneal membranes of patients undergoing PD and showed that the density of blood vessels per unit length of peritoneum was significantly higher for patients with peritoneal membrane function failure and was correlated with the degree of fibrosis. Furthermore, Zhu et al (2021) proved that Tetramethylpyrazine (TMP) treatment inhibited peritoneal angiogenesis and also ameliorated peritoneal thickening and collagen deposition. These findings suggest that antiangiogenic therapy may serve as a potential modality for preventing or reversing PF.…”
Section: Discussionmentioning
confidence: 99%